2017
DOI: 10.7717/peerj.3354
|View full text |Cite
|
Sign up to set email alerts
|

A new view on the morphology and phylogeny of eugregarines suggested by the evidence from the gregarineAncora sagittata(Leuckart, 1860) Labbé, 1899 (Apicomplexa: Eugregarinida)

Abstract: BackgroundGregarines are a group of early branching Apicomplexa parasitizing invertebrate animals. Despite their wide distribution and relevance to the understanding the phylogenesis of apicomplexans, gregarines remain understudied: light microscopy data are insufficient for classification, and electron microscopy and molecular data are fragmentary and overlap only partially.MethodsScanning and transmission electron microscopy, PCR, DNA cloning and sequencing (Sanger and NGS), molecular phylogenetic analyses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 85 publications
(161 reference statements)
4
54
0
Order By: Relevance
“…Comparisons to the 18S region alone of the queries (~1,200 bp) provided a similar overall topology to the combined tree, but with lower overall resolution (Figure S2). Furthermore, some key groups in the apicomplexan phylogeny were either missing or not supported by the 18S‐only tree, a pattern that was also recovered by previous analyses (Simdyanov et al, , ). Together, our phylogenetic comparisons revealed that 18S and 28S together provide increased resolution compared to 18S alone, but the differences between single‐ and two‐gene trees vary across groups.…”
Section: Discussionsupporting
confidence: 75%
“…Comparisons to the 18S region alone of the queries (~1,200 bp) provided a similar overall topology to the combined tree, but with lower overall resolution (Figure S2). Furthermore, some key groups in the apicomplexan phylogeny were either missing or not supported by the 18S‐only tree, a pattern that was also recovered by previous analyses (Simdyanov et al, , ). Together, our phylogenetic comparisons revealed that 18S and 28S together provide increased resolution compared to 18S alone, but the differences between single‐ and two‐gene trees vary across groups.…”
Section: Discussionsupporting
confidence: 75%
“…Biological and morphological studies have established that in gregarines, this apical complex is used for host cell attachment to allow the parasite to feed from its host cell by a process known as myzocytosis (Schrével et al., 2016; Simdyanov and Kuvardina, 2007). The host cell penetration by the parasite is not complete as the gregarine remains extracellular with only its apical end intimately engaged in a host–parasite interplay that has been studied at microscopic level but whose molecular actors are poorly defined (Valigurova et al., 2007; Schrével et al., 2016; Simdyanov et al., 2017). See also (Desportes and Schrével, 2013) for exhaustive descriptions of several additional examples.…”
Section: Why Should We Study Gregarines?mentioning
confidence: 99%
“…It is important here to indicate that there are alternative invasive modes in apicomplexan parasites such as Theileria and Cryptosporidium that differ from the better described Toxoplasma / Plasmodium mode (Gubbels and Duraisingh, 2012). What are the molecular similarities between the T. gondii and P. falciparum parasitophorous vacuole make up and the food vacuole of gregarines, that forms at the gregarine–host cell interface (Valigurova et al., 2007; Schrével et al., 2016; Simdyanov et al., 2017)? Or is the similarity stronger to the feeder organelle of epicellular Cryptosporidium ?…”
Section: Why Should We Study Gregarines?mentioning
confidence: 99%
See 2 more Smart Citations